2010
DOI: 10.1016/j.hal.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of hemolytic activity in the contact-dependent lethal effects of the dinoflagellate Karenia mikimotoi on the rotifer Brachionus plicatilis

Abstract: We investigated the effects of two strains (SUO-1 and FUK) of the dinoflagellate Karenia mikimotoi on the rotifer Brachionus plicatilis. The SUO-1 strain was highly toxic to rotifers, whereas the FUK strain was less toxic. After 10-hour incubations, the survivorship of rotifers exposed to SUO-1 and FUK was 20% and 95%, respectively.Both the cell-free culture supernatant and the ruptured cell suspension prepared from these strains were not toxic to rotifers. Furthermore, when direct contact between K. mikimotoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 38 publications
2
43
1
Order By: Relevance
“…Chattonella marina and Heterosigma akashiwo (Yang et al 1995;Ishimatsu et al 1996;Oda et al 1997). Zou et al (2010) indicated that ROS production depended on the K. mikimotoi strain and two other Japanese strains did not generate ROS. In the present Notes: LT 50 , least time for 50% of larvae to become moribund after exposure to specified cell concentration (mean 9 SEM from curve fit); LC 50 , lowest cell concentration for 50% of larvae to become moribund after exposure time of 2 or 24 h (estimate; 50% moribund defined as mean toxicity score of 2.5); , survival of all larvae at longest observation time or highest cell concentration used; 1 estimate (insufficient data for curve fit); 2 Pacific oyster; 3 Greenshell TM mussel.…”
Section: Habs Caused By Dinoflagellates In the Genusmentioning
confidence: 99%
See 2 more Smart Citations
“…Chattonella marina and Heterosigma akashiwo (Yang et al 1995;Ishimatsu et al 1996;Oda et al 1997). Zou et al (2010) indicated that ROS production depended on the K. mikimotoi strain and two other Japanese strains did not generate ROS. In the present Notes: LT 50 , least time for 50% of larvae to become moribund after exposure to specified cell concentration (mean 9 SEM from curve fit); LC 50 , lowest cell concentration for 50% of larvae to become moribund after exposure time of 2 or 24 h (estimate; 50% moribund defined as mean toxicity score of 2.5); , survival of all larvae at longest observation time or highest cell concentration used; 1 estimate (insufficient data for curve fit); 2 Pacific oyster; 3 Greenshell TM mussel.…”
Section: Habs Caused By Dinoflagellates In the Genusmentioning
confidence: 99%
“…Karenia mikimotoi is one of the most common fish-killing toxic dinoflagellates in both the Atlantic and Pacific regions (Honjo 1995;Silke et al 2005;Gentien et al 2007;Zou et al 2010). The cell concentration in a typical K. mikimotoi bloom can easily reach millions of cells per litre (1Á20)10 6 cells L Á1 ) (Silke et al 2005; International Council for the Exploration of the Sea 2006; Davidson et al 2009;Ulrich et al 2010).…”
Section: á1mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the activity of D-larvae and pre-settling larvae was significantly decreased following exposure to K. mikimotoi for 24 h at 5 Â 10 3 cells ml À1 and 24 h at 5 Â 10 2 cells ml À1 , respectively. No morphological anomalies were observed in embryos or in larvae, thereby excluding lytic activity in favor of toxicity of brevetoxins (PbTx) and/or other organic compounds, although K. mikimotoi is known to produce hemolysin activated via cell contact (Neely and Campbell, 2006;Zou et al, 2010). Brevetoxins (PbTx) responsible for the neurotoxic shellfish poisoning (NSP) in humans are produced by Karenia brevis, and other Kareniacea, including K. papilionacea, are suspected to produce PbTx or PbTx-like compounds (Furey et al, 2007;Ramsdell, 2008;Brand et al, 2012).…”
Section: Harmful Algal Species Treatmentsmentioning
confidence: 99%
“…Environmental differences in the water masses that led to the bloom occurring in some water masses and not others in the first place may also play a role. K. mikimotoi has also been observed to be toxic to rotifers (Zou et al, 2010) and have a negative effect on some ciliates (Hansen, 1995), however in some mesocosm experiments, reduction of grazing pressure has resulted in an increase in K. mikimotoi numbers (Turner and Graneli, 2006). It should also be noted that some dinoflagellate species can have an adverse impact on K. mikimotoi.…”
Section: Biotic Interactionsmentioning
confidence: 99%